The performance of 1, 3-dipropyl-2-(2-propoxyphenyl)-4, 5-diphenylimidazolium iodide based ionic liquid for biomass conversion into levulinic acid and formic acid. (November 2020) - Zunita, Megawati; Wahyuningrum, Deana; Buchari,; Bundjali, Bunbun; Gede Wenten, I.; Boopathy, Ramaraj
Graphical abstract: Highlights: [DPDIm]I based ionic liquid is a potential solvent and catalyst in bioprocessing. Ionic liquid in bioprocessing requires low temperature and less reaction time. Ionic Liquid catalyzed 94% of cellulose to levulinic acid (LA). Ionic liquid was recycled five times for the efficient production of LA. Abstract: Ionic liquid (IL) demonstrates better performance as a solvent in the biomass conversion process than conventional organic solvents. This study focuses on the application of new hydrophobic imidazolium-based IL as a solvent in biomass conversion process. A novel IL, namely, 1, 3-dipropyl-2-(2-propoxyphenyl)-4, 5-diphenylimidazolium iodide ([DPDIm]I), was synthesized and subsequently used as a solvent for biomass conversion to produce levulinic acid (LA) and Formic Acid (FA). The performance of [DPDIm]I supported by H2 SO4 as a solvent was shown by cellulose conversion into 94.23% of LA and 18.85% of FA at the optimum conditions of 140 °C temperature and the reaction time of two hours. A reusability test revealed the performance of [DPDIm]I as a solvent that can be recycled up to five times for biomass conversion.